Examining ownership of counterfeits: a Chinese perspective - Teah, Min; Phau, Ian (International Management Development Association, 2011)
Based on the theory of planned behaviour, the study explores the relationship between ownership and behavioural intentions towards counterfeits of luxury brands. Based on a sample of 202 Chinese respondents, the findings have revealed differences between ownership of counterfeits and behavioural intentions. As such, the study presents implications for practitioners and policy makers alike.